The crime of reckless driving with manifest disregard for life (Art. 381 CP): frontiers with eventual intent to commit homicide (art. 381 CP): fronteras con el dolo eventual homicida - Martín Ríos, Rocío (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2026)
The proliferation of "homicidal drivers" or "kamikaze drivers" on Spanish roads concerned the legislator to the point of introducing a specific offense into the Penal Code through the reform implemented in 2007: the crime of driving with manifest disregard for the lives of others. This provided more stringent punishments for the perpetrators of this particular form of road rage.Through a technical-legal analysis of the offense, this study aims to provide the keys to understanding the legal interests affected and to differentiate it from the basic offense of reckless driving. The main objective of this study will be the complex delimitation of this offense in relation to homicide committed with implied malice. The relative proximity between these two legal concepts has led to disparate judicial solutions that have required jurisprudential unification. An attempt will be made to establish indicators that allow for a more favorable classification towards one offense or the other.Special attention will be paid to the application of the concurrent offense rule established in Article 382 of the Spanish Penal Code, given the significance of its application when, in addition to the risk, a harmful result occurs.Finally, de lege ferenda proposals will be made to contribute to achieving the legal certainty to which the legal system should aspire.
Keywords: Reckless driving; manifest disregard; risk; eventual intent; homicide